2009
DOI: 10.1007/s11095-009-9885-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tape Stripping and Adjuvants on Immune Response After Intradermal DNA Electroporation

Abstract: Tape stripping is able to increase the Th1 immune response against both DNA and protein vaccines. Therefore, tape stripping appears to have interesting adjuvant effect on intradermal vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Skin GET can result in transfected cells in the epidermis, dermis, hypodermis, and even the muscle layer, dependent on the electrodes, injection techniques, animal species and plasmid designs used, for example whether tissue specific promoters are involved. GET with plate electrodes transfects cells to the mouse dermis [27], the epidermis of xenograft human skin [9], or both epidermis and dermis of rat [13]. GET with needle electrodes or needle arrays can reach the deep layers of the skin and result in transgenic cells in the dermis, epidermis, hypodermis and subcutaneous muscle layer of the mouse or rat [14], [28] or dermis of the pig [29].…”
Section: Discussionmentioning
confidence: 99%
“…Skin GET can result in transfected cells in the epidermis, dermis, hypodermis, and even the muscle layer, dependent on the electrodes, injection techniques, animal species and plasmid designs used, for example whether tissue specific promoters are involved. GET with plate electrodes transfects cells to the mouse dermis [27], the epidermis of xenograft human skin [9], or both epidermis and dermis of rat [13]. GET with needle electrodes or needle arrays can reach the deep layers of the skin and result in transgenic cells in the dermis, epidermis, hypodermis and subcutaneous muscle layer of the mouse or rat [14], [28] or dermis of the pig [29].…”
Section: Discussionmentioning
confidence: 99%
“…Salvioli and colleagues as well demonstrated improved intradermal penetration of heat-killed microorganisms of the antituberculosis vaccine in infants (Salvioli et al, 1952). Although HYA was proven to increase the efficacy of vaccines when used with both traditional (Bergqvist, 1950;Salvioli et al, 1952;Tozuka et al, 1954) and plasmid DNA vaccines (McMahon et al, 2001;Vandermeulen et al, 2009;Potter and Heller, 2011), no one studied its role when used in combination with ET. As a consequence, we asked whether exogenous HYA is able to affect skeletal muscle and may influence the muscle inflammatory reaction when used alone or with ET.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies demonstrated that an approximately 5-fold increase in expression of the gene of interest could be achieved after hyaluronidase muscle pretreatment (McMahon et al, 2001;Mennuni et al, 2002;Molnar et al, 2004). However, hyaluronidase did not improve transfection in skin (Vandermeulen et al, 2009). In tumors, where interstitial pressure is uniformly elevated and convection in the tumor tissue is negligible, the distribution of molecules relies on passive diffusion, which is mostly ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were done in muscle and skin (McMahon et al, 2001;Mennuni et al, 2002;Vandermeulen et al, 2009). The transfection efficiency was increased only in muscle.…”
mentioning
confidence: 99%